Long‐term outcome after stifle arthroscopy in 82 Western performance horses (2003–2010). Issue 6 (14th June 2019) - McCoy, Annette M.; Smith, Rebecca L.; Herrera, Stephanie; Kawcak, Christopher E.; McIlwraith, C. Wayne; Goodrich, Laurie R.
Abstract: Objective: To report the outcome of horses engaged in Western performance disciplines after stifle arthroscopy and identify prognostic factors for return to performance. Study design: Retrospective case series. Sample population: Eighty‐two Western performance horses undergoing stifle arthroscopy. Methods: Medical records were reviewed for horses involved in athletic performance/training for various Western performance disciplines and undergoing arthroscopy for lameness localized to the stifle. Follow‐up was obtained ≥2 years postoperatively by telephone interviews with the owners. Preoperative and intraoperative findings as well as postoperative treatment were analyzed for their association with return to athletic performance as the primary outcome of interest. Results: The most common disciplines represented were cutting (n = 38), Western pleasure (n = 13), and reining (n = 13). Approximately 40% (32/82) of horses returned to intended use after surgery. Increased age, higher degree of lameness, longer duration of lameness, and the presence of partial‐thickness cartilage lesions decreased the odds of returning to athletic performance. Postoperative therapies (intra‐articular: stem cells, corticosteroids, interleukin‐1 receptor antagonist protein, hyaluronic acid/polysulfated glycosaminoglycans; systemic: nonsteroid anti‐inflammatory drugs, hyaluronic acid/polysulfated glycosaminoglycans, oral joint supplements) did not affect the odds of returning to intended use. Conclusion: Less than half of the Western performance horses that underwent stifle arthroscopy returned to intended use. Older age, longer duration of lameness, and presence of partial‐thickness cartilage lesions affected the odds of a horse returning to intended use. Postoperative therapies did not affect the outcome in this population. Clinical significance: The prognosis of Western performance horses undergoing stifle arthroscopy is as guarded as that previously reported in horses of other disciplines.